METHODOLOGY OF ORGANIZATION OF GAME ACTIVITY IN JUNIOR, MIDDLE AND SENIOR AGE - O.S. Korovkina (Academy of Cognitive and Natural Sciences, 2010)
The article depicts the methods of organizations of playing activity at the English les sons in younger , average and senior school age.